EARTHWORM BIODIVERSITY OF JHARKHAND : TAXONOMIC DESCRIPTION - M. P. SINHA; SRIVASTAVA, ROHIT; D. K. GUPTA (The Bioscan, 2013)
Earthworms were collected from different habitats viz. agroecosystems, grassland, pasture, forest and garbage sites form different parts of Jharkhand. A total of 15 species of earthworm were identified namely Glyphidrilus tuberosus (Stephenson), Eisenia foetida (Savingny)Pontoscolex corethrurus (Michaelsen), Dichogaster affinis (Michaelsen), Dichogaster bolaui (Michaelsen), Lennogaster pusillus (Stephenson), Pellogaster bengalensis (Michaelsen), Ocnerodrilus occidentalis (Eisen), Lampito mauritii (Kinberg), Pheretima planata (Gates), Pheretima posthuma (Vaillant), Perionyx sansibaricus (Michaelsen), Perionyx excavatus (Michaelsen)Drawida calebi (Gates) and Drawida willsi (Michaelsen) have been identified belonging to 6 families and 9 genera.